The material culture of writing - Alexix, Cydney, editor; Rule, Hannah J., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
This book opens up avenues for understanding writing through scholarship in material culture studies. Contributors each interrogate an object, set of objects, or writing environment to reveal the sociomaterial contexts from which writing emerges. Close study of such artifacts offers up the potential for inquiry into writing artifacts and environments.--Provided by publisher.
Introduction: the material culture of writing / Cydney Alexis and Hannah J. Rule -- The symbolic life of the Moleskine notebook: material goods as a tableau for writing identity performance / Cydney Alexis -- Black ink, white bodies: gender, race and writing instruments / Desirée Henderson -- Indexical heirlooms in immigrant literacy history narratives / Jenny Krichevsky -- Material motherhood: the disconnect of science and consumerism from nostalgia in baby books / Emilie Merrigan -- New writing in new spaces: 'social writing' in an interdisciplinary academic makerspace / Debby Andrews -- 'Every convenience for a man of letters': Thomas Jefferson's writing suite / Diane Ehrenpreis -- Assembling the file, or, How conservation works / Anne Mackay -- The Victorian visitor's book as genre and artifact / Kevin James -- Gendered letterwriting in Renaissance England: genre as sociomaterial action / Keri Epps.
Keywords: Written communication -- Social aspects; Writing materials and instruments -- Social aspects; Authorship -- Technique; Writing -- Social aspects; Material culture -- Study and teaching